KONTRIBUSI HUTAN RAKYAT TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI DESA RUMOONG ATAS KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - Astriani Mohtar; Hengki D. Walangitan; Theodora M. Katiandagho (COCOS, 2018)
ABSTRAK According to Handoko (2007), income from community forests for farmers is still positioned as side income with a range of more than 10% of total income. The amount of contribution and the amount of income that cannot be received sustainably shows that community forests have not been able to become the foundation of farmer household livelihood, so research is needed on how much community forest contribution to farmer household income in Rumoong Atas Village, Tareran District, South Minahasa Regency. The objectives of this study were to describe the community forest management system in Rumoong Atas Village and to discover the contribution of the results of community forest management specifically for timber production to the income of farmer households data collection was carried out using the observation method, interviews with 30 respondents who were deliberately selected (purposive sampling) and literature studies to obtain primary data and secondary data. The results shows that 1) The community forest management system in Rumoong Atas Village uses an agroforestry system and develops a monoculture cropping pattern and mixed crops. Management activities are carried out based on three subsystems, which are carried out all with a free scale. The type of wood planted depends on seeds provided by the government. The harvest period is adjusted to the needs. 2) The contribution of the average income of community forests to the income of farmer households in Rumoong Atas Village is respectively (58.25%) for strata I, strata II (81.79%) and strata III (80.40%). The size of the community forest contribution depends on the number of trees that exist. Kata Kunci: Desa Rumoong Atas, Hutan Rakyat, kontribusi, pendapatan, rumah tangga